Analisa Faktor Ergonomi dengan Metode Nordic Body Map untuk Pekerja di Industri Tahu CV. Budi Sari Jaya Sidoarjo - Putri Ekawati Ariyantono (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Tofu is a typical Indonesian dish that is well known and has many Indonesian fans who are accustomed to consuming it as a side dish or as a snack food among young people and adults. The tofu processing process at the tofu factory is the majority still using the manual method. Workers sometimes feel tired when carrying out their work activities, if they forced to work continuously then fatigue will increase or they can be at risk of injury and later, it will have a bad impact on the workers. The population in this research is as many as 10 workers in the burning, washing , milling, cooking, to the printing of tofu. Data collection begins by using a site survey in the field and then analyzing the potential hazards in the production process. The data collection instrument used to determine the conditions experienced by workers is the Nordic Body Map. In addition, interviews were also conducted with workers regarding age, length of work, smoking habits of workers, and injuries experienced by workers. The purpose of this study was to identify musculoskeletal complaints in workers. The results showed that there were inadequate working conditions because at the time of the tofu making process they still used the manual method and the musculoskeletal complaints of the workers were in the moderate category. The prevention that can be done is providing drinking water, adding rest areas and stretching muscles before, during and after work